Chromosomal characterization of Pseudonannolene strinatii (Spirostreptida, Pseudonannolenidae) - Campos, Kleber Agari [UNESP]; Fontanetti, Carmem S. [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2004)
The chromosomes of the cave millipede Pseudonannolene strinatii Mauriès, 1974 were investigated. The diploid chromosome number was found to be 2n=16, XX/XY; the C-banding technique revealed a large amount of heterochromatin while the silver staining technique (Ag-NOR) evidenced the presence of heteromorphism of the NORs in some cells.
Keywords: Diplopoda; cytogenetics; caves; heterochromatin